Cayman Islands Sea Turtle Nesting Population Increases Over 22 Years of Monitoring - Blumenthal, Janice M.; Hardwick, Jane L.; Austin, Timothy J.; Broderick, Annette C.; Chin, Paul; Collyer, Lucy; Ebanks-Petrie, Gina; Grant, Leah; Lamb, Lorri D.; Olynik, Jeremy; Omeyer, Lucy C. M.; Prat-Varela, Alejandro; et al. (Frontiers in Marine Science, 2021)
Given differing trajectories of sea turtle populations worldwide, there is a need to assess and report long-term population trends and determine which conservation strategies are effective. In this study, we report on sea turtle nest monitoring in the Cayman Islands over a 22-year period. We found that green (Chelonia mydas) and loggerhead (Caretta caretta) nest numbers increased significantly across the three islands since monitoring began in 1998, but that hawksbill nest numbers remained low with a maximum of 13 nests recorded in a season. Comparing the first five years of nest numbers to the most recent five years, the greatest percentage increase in green turtle nests was in Grand Cayman from 82 to 1005 nests (1126%), whereas the greatest percentage increase for loggerhead turtle nests was in Little Cayman from 10 to 290 nests (3800%). A captive breeding operation contributed to the increase in the Grand Cayman green turtle population, however, loggerhead turtles were never captive-bred, and these populations began to increase after a legal traditional turtle fishery became inactive in 2008. Although both species have shown significant signs of recovery, populations remain at a fragment of their historical level and are vulnerable to threats. Illegal harvesting occurs to this day, with multiple females taken from nesting beaches each year. For nests and hatchlings, serious threats include artificial lighting on nesting beaches, causing hatchlings to misorient away from the sea, and inundation of nests by seawater reducing hatch success. The impacts of lighting were found to increase over the monitoring period. Spatial data on nest distribution was used to identify critical nesting habitat for green and loggerhead turtles and is used by the Cayman Islands Department of Environment to facilitate remediation of threats related to beachside development and for targeted future management efforts.